English Language Teaching through Literature at University level an experimental study - Shriganeshan, K. (M.Phil. in Linguistics, 1999)
People in the Jaffna district began learning English almost two Centuries ago. When the swabasha movement gained momentum by 1956 in Sri Lanka, the English language lost its place of dominance as official language. This led to deterioration in the standard of English among students. The motivation of the students and teachers in the learning and teaching of English respectively was found to be minimal. Despite different methods such as the Direct Method, the Grammar Translation Method, the Graded Structural-oral situational approach and the communicative approach adopted by the educationists at different times the proficiency attained by the students did not improve. The present study gives an account of the status of English in Sri Lanka during the colonial period and after independence and analyses the reasons for the failure in successful learning of English in schools and Universities. The study makes a review of the place of literature in a second language curriculum and presents a detail account of experimental language teaching making use of literary pieces in a University classroom. The study ends with an analysis of errors committed by students and makes recommendations to improve English Language teaching at University level.